2019
DOI: 10.1016/j.egja.2018.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative effects of desflurane versus propofol on hemostasis guided by thromboelastometry in splenectomy with liver cirrhosis

Abstract: Background: Cirrhotic patients have impaired hemostasis with variable incidence of hypersplenism necessitating splenectomy. Rotation thromboelastometery (ROTEM) facilitates diagnosis and guides management. This study evaluates perioperative effects of desflurane versus propofol on hemostasis in cirrhotic patients undergoing splenectomy guided by ROTEM and laboratory hemostatic tests. Methods: Thirty hepatic Child A patients, ASA II-III, of either sex, aged 25-55 years, undergoing splenectomy were randomly allo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 32 publications
(37 reference statements)
1
2
0
Order By: Relevance
“…ALT and AST showed statistically significant increase in postoperative values compared to preoperative values in both sevoflurane and desflurane groups. In line with our study, Khafagy et al (8) investigated the effect of desflurane versus propofol with total intravenous anesthesia (TIVA Both studies, ours and Khafagy, the changes detected were all within the normal reference range. Their study also showed that PT & INR, were increased immediate postoperative then decreased 24 hours postoperative.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…ALT and AST showed statistically significant increase in postoperative values compared to preoperative values in both sevoflurane and desflurane groups. In line with our study, Khafagy et al (8) investigated the effect of desflurane versus propofol with total intravenous anesthesia (TIVA Both studies, ours and Khafagy, the changes detected were all within the normal reference range. Their study also showed that PT & INR, were increased immediate postoperative then decreased 24 hours postoperative.…”
Section: Discussionsupporting
confidence: 87%
“…On the contrary, in our study, both fibrinogen and platelets decreased immediate postoperative, then further decreased 24 hours postoperative. The difference between Khafagy's study and ours may be due to differences in the type of patient as Khafagy et al (8) , did their in patients with livercirrhosis who were being scheduled for splenectomy, which may explain the postoperative increase in platelet counts. Khafagy et al (8) detected immediate postoperative reduction of hemoglobin, followed by a further 24-hour postoperative decrease.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation